Development of flexible piezoelectric energy harvester for wearable device - Muhammad Irsyad Suhaimi (Kulliyyah of Engineering, Interational Islamic University Malaysia, 2020)
Recent advancements in sensing technology and wireless communications have accelerated the development of the Internet of Things (IoT) and wearable sensors. An emerging trend self-powered wearable devices, which eliminates the necessity of the user to carry bulky batteries. In this work, the development of a flexible piezoelectric energy harvester that is capable of harvesting energy from low-frequency vibration is presented. It was designed with a cantilever structure of PET/AZO/Ag layers in d33 mode which can generate large output voltages with small displacements. Aluminium doped to ZnO (AZO) piezoelectric layers was chosen due to its low deposition temperature and no requirements of post-deposition annealing and poling compared to other materials. Two significant design parameters were chosen, namely the effect of the gap between electrodes and the number of interdigitated electrodes (IDE) pairs to the output voltage and resonant frequency. These two parameters have been simulated using a finite element simulation tool named COMSOL Multiphysics. The device was then fabricated by sputtering the AZO thin film followed by screen printing of the silver IDE pairs. The sputtered AZO on PET showed c-axis orientation at 002 peak with 2θ values of 34.45° which indicates piezoelectric behavior. The average measured d33 constant value was 1.8 pC/N. The energy harvester was capable of generating 0.867 Vrms output voltage when actuated at 49.6 Hz. This indicates that the AZO thin films with printed silver electrodes have the potential to be used as a flexible, d33 energy harvester for wearable sensors.